2005
DOI: 10.4065/80.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Nonischemic Central Retinal Vein Occlusion Associated With Celiac Disease

Abstract: syndrome caused by membranous obstruction of the inferior vena cava associated with coeliac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Thrombophilia may result from hyperhomocysteinemia and deficiencies in protein S, folate, and vitamin B2[ 40 - 42 ]. The thrombotic events in CD may also result from dehydration due to diarrhea[ 43 ]. Cerebral venous sinus thrombosis can occur in CD patients[ 40 , 44 - 46 ], even in absence of gastrointestinal symptoms[ 45 ], but can resolve with symptomatic treatment[ 40 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%
“…Thrombophilia may result from hyperhomocysteinemia and deficiencies in protein S, folate, and vitamin B2[ 40 - 42 ]. The thrombotic events in CD may also result from dehydration due to diarrhea[ 43 ]. Cerebral venous sinus thrombosis can occur in CD patients[ 40 , 44 - 46 ], even in absence of gastrointestinal symptoms[ 45 ], but can resolve with symptomatic treatment[ 40 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%
“…[88][89][90] Only a few case reports have included patients with thrombosis on the arterial side of the circulation, and in those cases the role of CD in the mechanism of the thrombosis was uncertain. [91][92][93] Coagulopathy CD can be associated with abnormalities in coagulation factors resulting in an abnormal bleeding tendency. Malabsorption of vitamin K is common in chronic gastrointestinal disorders.…”
Section: Venous and Arterial Thromboembolismmentioning
confidence: 99%
“…Studies have shown that prothrombotic risk factors are addi- tive; therefore, patients with MS may be predisposed, and the addition of interferon treatment and other factors may cause thrombosis. 11,12 Interferon-␣-associated retinopathy has been reported to resolve spontaneously, usually not requiring discontinuation of treatment. Treatment was continued in all our cases, and the microvascular changes seen in two patients persisted ( Table 1).…”
Section: Discussionmentioning
confidence: 97%